Transformasi Media Pembelajaran Sebagai Penyalur Pesan - Syamsiani Syamsiani (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to determine the transformation of learning media as message distributors. The study in this paper uses a descriptive method with literature study, namely by presenting an overview and analysis of the meaning, rationale for using media, rationale for using media, learning media in the perspective of the Qur'an and Hadith and the benefits of using media. The results of this literature review indicate that learning media in general are tools for teaching and learning processes. Everything that can be used to stimulate the thoughts, feelings, attention and abilities or skills of the learner so that it can encourage the learning process. This limitation is quite broad and in-depth covering the understanding of resources, environment, people and methods used for learning/training purposes.